Synthesis and biological evaluation of pyridylpiperazine hybrid derivatives as urease inhibitors - Akash, Muhammad; Zaib, Sumera; Ahmad, Matloob; Sultan, Sadia; Al-Hussain, Sami A. (Frontiers in Chemistry, 2024)
Urease, a nickel-dependent enzyme found in various life forms, catalyzes urea breakdown, concluding nitrogen metabolism by generating ammonia and carbamate. This process causes a rise in pH, supports the survival of pathogens, and can lead to infections such as gastric disorders like ulcers and cancer in humans. Helicobacter pylori employs urease for survival in the acidic environment of the stomach and in protein synthesis. To treat such infections and inhibit the growth of pathogens, it is mandatory to obstruct urease activity; therefore, derivatives of 1-(3-nitropyridin-2-yl)piperazine were synthesized (5a-o; 7a-k). All these newly synthesized compounds were investigated for urease inhibition by in vitro inhibition assays. The results showed that 5b and 7e are the most active inhibitors, having IC50 values of 2.0 ± 0.73 and 2.24 ± 1.63 µM, respectively. These IC50 values are lower than the IC50 value of the standard thiourea, which was 23.2 ± 11.0 µM. The hemolysis potential of 5b, 5c, 5i, 7e, and 7h was also determined; 7e and 7h exhibited good biocompatibility in human blood cells. Through in silico analysis, it was shown that both these potent inhibitors develop favorable interactions with the active site of urease, having binding energies of −8.0 (5b) and −8.1 (7e) kcal/mol. The binding energy of thiourea was −2.8 kcal/mol. Moreover, 5b and 7e have high gastrointestinal permeability as predicted via computational analysis. On the other hand, the IC50 value and binding energy of precursor compound 3 was 3.90 ± 1.91 µM and −6.1 kcal/mol, respectively. Consequently, 5b and 7e can serve as important inhibitors of urease.